Motivasi Kerja Dan Sistem Kompensasi Pengaruhnya Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada BRI Unit Kinali Dan BRI Unit Sungai Aur Kabupaten Pasaman Barat - Yerismal; Jamil, Muhammad; Rahman, Ahmad Fajri (Journal of Science Education and Management Business, 2022)
This study aims to test how much influence the work motivation and compensation system has on employee performance with job satisfaction as an intervening variable at BRI Unit Kinali and BRI Unit Sungai Aur, West Pasaman Regency. Methods of data collection through surveys and distributing questionnaires, with a sample of 36 respondents. The sampling technique used is probability sampling with a stratified random sampling model. The analysis method used is multiple linear regression analysis and path analysis using SPSS for windows version 16.0.Based on the research results indicate that 1). Obtained a positive and significant influence between Work Motivation on Job Satisfaction. 2). Obtained a positive and significant influence between the Compensation System on Job Satisfaction. 3). Obtained a positive and significant influence between Work Motivation on Employee Performance. 4). Obtained positive and significant influence between the Compensation System on Employee Performance. 5). Obtained a positive and significant influence between Job Satisfaction on Employee Performance. 6). Job Satisfaction is able to mediate Work Motivation on Employee Performance. 7). Job Satisfaction is able to mediate the Compensation System on Employee Performance. Finally, the authors suggest to the management of BRI Unit Kinali and BRI Unit Sungai Aur, West Pasaman Regency to be able to increase Employee Performance, it is necessary to increase Job Satisfaction by increasing its indicators. And to increase job satisfaction, it is necessary to increase the Work Motivation and Compensation System through improving the indicators